Population dynamics of fruit flies of the genus Anastrepha (dip., tephritidae) in the "Recôncavo Baiano", state of Bahia, Brazil. II - Population fluctuation - Nascimento, A.S. do; Zucchi, R.A.; Morgante, J.S.; Malavasi, A. (Pesquisa Agropecuaria Brasileira, 2014)
Population fluctuation of the five commonest species of the genus Anastrepha: A. fraterculus, A. obliqua, A. sororcula, A. distincta and A. serpentina, in five localities in the Recôncavo Baiano, State of Bahia, Brazil, was studied. The species A. obliqua was predominant in citrus orchards, A. fraterculus prevails in the localities with tropical hosts, with preference for guava trees. The occurrence of these species in citrus cultivars was coincidental with fructification of these plants. This was not observed for tropical hosts, and the incidence of A. fraterculus was found to be high in guava trees even in the absence of fruit. The collect was influenced by the mean and maximum temperatures, and relative humidity. The minimum temperature and rain precipitation did not show any effect. The occurrence of Ceratitis capitata, in the Recôncavo Baiano, was also discussed.